Prosopis juliflora as a new cosmetic ingredient: Development and clinical evaluation of a bioactive moisturizing and anti-aging innovative solid core - Damasceno, Gabriel A. B.; Barreto, Stella M. A. G.; Reginaldo, Fernanda P. S.; Souto, Augusto L.; Negreiros, Marilia M. F.; Viana, Rony L. S.; Pinto, Talita K. B.; Daher, Claudia C.; Silva-Filho, Jean A. A.; Moura, Rafael A. O.; Silva, Milena A.; Silveira, Walteca L. L.; et al. (Elsevier B.V., 2020)
Prosopis juliflora is an invasive plant distributed throughout the world and presents metabolites of interest for cosmetology. The aim of this work was to develop a new polysaccharide-based ingredient from P. juliflora and analyze its application in a solid core formulation that upon contact with water instantly forms a gel to improve moisturizing and anti-aging skin properties. Purified extracts by gel chromatography were characterized by NMR and LC-DAD-MS-MS. The in vitro and in vivo safety, antioxidant activity, formulation development and clinical evaluation were performed. The extract was characterized as containing an a-glucan and phenolics. It was non-cytotoxic, non-phototoxic and no skin reactions were observed in vivo. Antioxidant activity were present through different mechanisms. Clinical evaluation reinforced the potential of P. juliflora in skin hydration and microrelief improvement. This innovative form proved to be a prototype of a new product and the first study of an a-glucan as a cosmetic ingredient.
Keywords: Algaroba; Anti-aging; Cosmetics; Fabaceae; Moisturizing; Polysaccharides; Prosopis juliflora